Temporomandibular joint in juvenile idiopathic arthritis: magnetic resonance imaging measurements and their correlation with imaging findings - Calle, Alison Jhisel Mansmith; Ogawa, Celso Massahiro; Martins, Jaqueline Serra; Santos, Fernanda Cardoso; de Castro Lopes, Sérgio Lucio Pereira [UNESP]; Nahás-Scocate, Ana Carla Raphaelli; Hasseus, Bengt; Appenzeller, Simone; Costa, Andre Luiz Ferreira (Springer Nature, 2021)
Objective: The aim of this study was to investigate the TMJ components in patients with juvenile idiopathic arthritis (JIA) and to compare them with a control group based on magnetic resonance imaging (MRI) measurements. Methods: This study comprised an assessment of MRI measurements of 96 temporomandibular joints (TMJ) following classification criteria set by the International League of Associations for Rheumatology (ILAR). Three measurements were considered for study: condyle excursion angle (CEA), height of articular eminence (HAE) and inclination of articular eminence (IAE). All TMJs were assessed by linear measurements made by using the OnDemand 3D software. The comparison between the groups was performed by using Mann–Whitney’s test. Results: Lower measurement values were found for IAE, HAE and CEA in JIA patients (P-values < 0.001, 0.005 and < 0.001, respectively). Conclusion: The study showed the differences in MRI measurements between JIA patients and controls, with the former with the lowest indices.
Keywords: Head and neck; Magnetic resonance imaging; Osteoarthritis; Synovitis; Temporomandibular joint assessment